Developing Teacher Professional Identity through Classroom Action Research in Indonesian EFL Context - Silva Fadilah Suparman; Izza Aisyah Nurmahati (ANTHOR: Education and Learning Journal, 2026)
The growing discussion on teacher professional identity reflects a broader understanding that becoming a teacher extends well beyond acquiring pedagogical knowledge or mastering classroom techniques. However, much less attention has been paid to how guided reflection contributes to the development of professional identity. This study explored how Indonesian EFL pre-service teachers reflected on their experiences after completing Classroom Action Research projects and how those experiences shaped their developing professional identities. This study employed a qualitative approach. Data were collected from the written reflections of 36 Indonesian EFL pre-service teachers and analysed using Reflexive Thematic Analysis. The analysis showed that participants gradually developed their professional identities by adopting a more inquiry-oriented approach to teaching, learning from classroom experience, becoming more aware of themselves and their students, and recognising the importance of collaboration with colleagues. These findings suggest that Classroom Action Research could be included in one of many initial teacher education programs to develop pre-service teachers' professional identity. Furthermore, guided reflection could be conducted to clearly see how it shapes their professional identities.  However, this study only covered Indonesian EFL pre-service teachers of a single university and utilized guided reflection questions. Future research could conduct further research using various kinds of instruments, such as a questionnaire, a reflection journal, or even an in-depth interview, to get a much richer description of how EFL pre-service teacher develop their professional identity.